Association between Family Dysfunction and Post-Traumatic Stress Disorder in School Students during the Second COVID-19 Epidemic Wave in Peru - Fernandez-Canani, Maria A. (2022)
“Although the effect of the COVID-19 pandemic on children and adolescents’ mental health has been studied, there is still scarce evidence of the influence of nuclear family on the development of post-traumatic stress disorder (PTSD). This study aimed to determine the association between family dysfunction and PTSD in Peruvian high-school students during the COVID-19 pandemic. A cross-sectional study was conducted using a virtual survey administered to 562 high-school students in three schools in Chiclayo, Peru. The dependent variable was PTSD, which was measured with the Child PTSD Symptom Scale. Family dysfunction was the main independent variable, measured with the Family APGAR Questionnaire. Prevalence ratios (PR) and 95% confidence intervals (95% CI) were estimated with generalized linear models. Most of the students were female (88.3%) and the average age was 14.4 years. We found that 21.4% showed severe family dysfunction and 60.3% had PTSD. Students with mild and moderate family dysfunction had 37% (PR: 1.37; 95% CI: 1.14–1.65) and 26% (PR: 1.26; 95% CI: 1.04–1.54) higher PTSD prevalence, respectively. In conclusion, family dysfunction may influence the development of PTSD in adolescents. This study suggests the importance to develop a healthy family environment to help adolescents face critical situations experienced during the pandemic“